Investigation of Corn Seeds Growth under Simulated Microgravity - Oluwafemi, F. A.; Olubiyi, R. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Living organisms are made-up of cells, while cells are made-up of several macromolecules such as proteins, carbohydrates, nucleic-acids, lipids, which have individual functions. The role and impact of light on plant metabolism including photosynthesis cannot be overemphasized. Corn seeds were planted in two petri-dishes using plant-agar after standard-preparation. The plant-agar served as soil and as source of nutrient. The two petri-dishes containing the seeds, had equal treatment by receiving 50lux of light and humidity of 60-100%. These are the essential conditions for photosynthesis. After 3days, germination of the seeds was observed. One of the petri-dishes was labelled terrestrial-control while the other was labelled clinorotated. The clinorotated was mounted on clinostat, a microgravity-simulating equipment for 4 hours. The two petri-dishes for the 4 hours received 50lux of light. Observations and analysis were carried out using ImageJ software on pictures taken periodically from the two samples. The quantitative result of the analysis showed that the clinorotated sample had 9.73mm/h growth-rate while terrestrial-control sample had 7.54mm/h growth-rate. The two samples received equal lux of light, but the interaction of the light for conversion into chemical-energy for plant-activities was different after subjection to simulated-microgravity for 4 h. It could be deduced that: the light dependent reactions, which take place in the thylakoid-membrane, that use light-energy to make ATP (chemical) and NADPH was speed-up under simulated-microgravity and that photosynthetic functions were impacted positively by the space-environment. Therefore, role of light on plants is complex and this is a function of the role of complex light interactions on individual cells of plant.